(untitled) (The Review of Diabetic Studies, 2025)
Background: Ensuring patient safety and improving healthcare quality have become global priorities, yet challenges persist in translating knowledge into practice. Interprofessional collaboration among healthcare administrators, nurses, midwives, and patient safety professionals is vital for sustaining a culture of safety. Despite national reforms under Saudi Vision 2030, limited evidence exists on how these groups collectively perceive and apply patient safety principles. Objective: This systematic review aimed to synthesize evidence on the knowledge, attitudes, and practices (KAP) toward quality and patient safety among healthcare administrators, nurses, midwives, and patient safety professionals in Saudi Arabia. Methods: A systematic literature review was conducted following PRISMA 2020 guidelines. Electronic databases—PubMed, Scopus, CINAHL, and the Saudi Digital Library—were searched for studies published between 2000 and 2024. Seventeen eligible studies were analyzed using thematic narrative synthesis. Data extraction focused on KAP domains, professional categories, and contextual determinants. Results: Findings revealed that most healthcare professionals demonstrated moderate knowledge, positive attitudes, and variable practices toward patient safety. Training and experience were the strongest predictors of improved KAP outcomes. However, punitive reporting systems, limited leadership support, and weak interprofessional collaboration were recurrent barriers. Nurses displayed higher practical engagement, while administrators and midwives remained underrepresented in research. Conclusion: The review highlights the need for comprehensive, interprofessional safety training and leadership-driven reforms to foster a non-punitive culture and enhance safety practices. Integrating standardized patient safety curricula and continuous KAP evaluation into Saudi healthcare institutions could substantially strengthen safety culture and advance the goals of Vision 2030.